Двохетапне випікання хліба з використанням проміжного вакуумно-випарного охолодження - Ковальов, Олександр Володимирович; Миколів, Іван Михайлович; Бабко, Євген Миколайович; Якобчук, Роман Леонідович (My University, 2015)
Розглянуто й охарактеризовано «двохетапне» випікання з використанням проміжного вакуумно-випарного охолоджування, що дає змогу допікати хліб безпосередньо на місці реалізації. Для можливості впровадження цієї технології було розроблено фізичну і математичну моделі процесу, що продемонстровано в даній роботі. Визначено оптимальний час попереднього випікання. Technology of bread production is time consuming and quite a long process. Due to the fact that this process includes many manufacturing operations, changes in length which leads to deterioration of product quality, traditional technology remained unchanged for a long time. This led to the limitation of range of bakery products; and the absence of fresh hot bread in the early hours; the creation of night shift and increase the burden on bakers working the night shift; and the lack of fresh bread at remote points of supply and trade. These problems caused by the continuity and long-term process of bakery products division helped to decide on the bread baking process steps for the increase or decrease of the length of intermediate processes that would allow the technology to make more flexible simultaneously reducing the quality of baked bread.
Keywords: випікання хліба; вакуум-випарне охолодження; vacuum evaporative cooling; baking bread; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра машин і апаратів харчових та фармацевтичних виробництв